Genetic dissection of theta rhythm heterogeneity in mice - Shin, J; Kim, D; Bianchi, R; Wong, RKS; Shin, HS (NATL ACAD SCIENCES, 2005)
Rhythmic oscillatory activities at the theta frequency (4-12Hz) in the hippocampus have long-attracted attention because they have been implicated in diverse brain functions, including spatial cognition. Although studies based on pharmacology and lesion experiments suggested heterogeneity of these rhythms and their behavioral correlates, controversies are abundant on these issues. Here we show that mice harboring a phospholipase C (PLC)-beta 1(-/-) mutation (PLC-beta 1(-/-) mice) lack one subset of theta rhythms normally observed during urethane anesthesia, alert immobility, and passive whole-body rotation. In contrast, the other subset of theta rhythms observed during walking or running was intact in these mutant mice. PLC-beta 1(-/-) mice also have somewhat disrupted theta activity during paradoxical sleep but do have an atropine-resistant component of theta rhythm. In addition, carbachol-induced oscillations were obliterated in hippocampal slices of PLC-beta 1(-/-) mice. Interestingly, PLC-beta 1(-/-) mice showed deficits in a hidden platform version of the Morris water maze yet performed well in motor coordination tests and a visual platform version of the Morris water maze. The results genetically define the existence of at least two subtypes of theta rhythms and reveal their association with different behaviors.
Keywords: METABOTROPIC GLUTAMATE RECEPTORS; PHOSPHOLIPASE-C ISOZYMES; HIPPOCAMPAL EEG; RAT HIPPOCAMPUS; CA3 REGION; H-CURRENT; IN-VITRO; OSCILLATIONS; BEHAVIOR; NEURONS